Improving the Quality of Dentistry (IQuaD): a cluster factorial randomised controlled trial comparing the effectiveness and cost–benefit of oral hygiene advice and/or periodontal instrumentation with routine care for the prevention and management of periodontal disease in dentate adults attending dental primary care - Ramsay, Craig R; Clarkson, Jan E; Duncan, Anne; Lamont, Thomas J; Heasman, Peter A; Boyers, Dwayne; Goulão, Beatriz; Bonetti, Debbie; Bruce, Rebecca; Gouick, Jill; Heasman, Lynne; Lovelock-Hempleman, Laura A; et al. (Health technology assessment (Winchester, England), 2018)
Periodontal disease is preventable but remains the most common oral disease worldwide, with major health and economic implications. Stakeholders lack reliable evidence of the relative clinical effectiveness and cost-effectiveness of different types of oral hygiene advice (OHA) and the optimal frequency of periodontal instrumentation (PI). To test clinical effectiveness and assess the economic value of the following strategies: personalised OHA versus routine OHA, 12-monthly PI (scale and polish) compared with 6-monthly PI, and no PI compared with 6-monthly PI. Multicentre, pragmatic split-plot, randomised open trial with a cluster factorial design and blinded outcome evaluation with 3 years' follow-up and a within-trial cost-benefit analysis. NHS and participant costs were combined with benefits [willingness to pay (WTP)] estimated from a discrete choice experiment (DCE). UK dental practices. Adult dentate NHS patients, regular attenders, with Basic Periodontal Examination (BPE) scores of 0, 1, 2 or 3. Practices were randomised to provide routine or personalised OHA. Within each practice, participants were randomised to the following groups: no PI, 12-monthly PI or 6-monthly PI (current practice). Clinical - gingival inflammation/bleeding on probing at the gingival margin (3 years). Patient - oral hygiene self-efficacy (3 years). Economic - net benefits (mean WTP minus mean costs). A total of 63 dental practices and 1877 participants were recruited. The mean number of teeth and percentage of bleeding sites was 24 and 33%, respectively. Two-thirds of participants had BPE scores of ≤ 2. Under intention-to-treat analysis, there was no evidence of a difference in gingival inflammation/bleeding between the 6-monthly PI group and the no-PI group [difference 0.87%, 95% confidence interval (CI) -1.6% to 3.3%; = 0.481] or between the 6-monthly PI group and the 12-monthly PI group (difference 0.11%, 95% CI -2.3% to 2.5%; = 0.929). There was also no evidence of a difference between personalised and routine OHA (difference -2.5%, 95% CI -8.3% to 3.3%; = 0.393). There was no evidence of a difference in self-efficacy between the 6-monthly PI group and the no-PI group (difference -0.028, 95% CI -0.119 to 0.063; = 0.543) and no evidence of a clinically important difference between the 6-monthly PI group and the 12-monthly PI group (difference -0.097, 95% CI -0.188 to -0.006; = 0.037). Compared with standard care, no PI with personalised OHA had the greatest cost savings: NHS perspective -£15 (95% CI -£34 to £4) and participant perspective -£64 (95% CI -£112 to -£16). The DCE shows that the general population value these services greatly. Personalised OHA with 6-monthly PI had the greatest incremental net benefit [£48 (95% CI £22 to £74)]. Sensitivity analyses did not change conclusions. Being a pragmatic trial, we did not deny PIs to the no-PI group; there was clear separation in the mean number of PIs between groups. There was no additional benefit from scheduling 6-monthly or 12-monthly PIs over not providing this treatment unless desired or recommended, and no difference between OHA delivery for gingival inflammation/bleeding and patient-centred outcomes. However, participants valued, and were willing to pay for, both interventions, with greater financial value placed on PI than on OHA. Assess the clinical effectiveness and cost-effectiveness of providing multifaceted periodontal care packages in primary dental care for those with periodontitis. Current Controlled Trials ISRCTN56465715. This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in ; Vol. 22, No. 38. See the NIHR Journals Library website for further project information.